Mapping The Landscape of Performance on Budgetary Slack Research: Analysis Using VOSViewer - Desriani, Neny; Maheswari, Fidela Salsabilla; Mirza. BR, Aryan Danil; Saputra, M Rizky Rico; Handayani, Putri; Al-ghifari, Abidzar Septawandra (FKIP Universitas Lampung, 2024)
This study aims to identify the development map of research related to performance on budgetary slack by using bibliometric analysis methods to assess bibliographic data, including the number of authors, number of journals, and keywords of articles. This study uses article publication data from 1981-2023 in research on the theme